Elektroplating Eksperimen Sebagai Penguatan Konsep Elektrokimia - Asworo, Yuliana Dwi (LPPM Universitas Negeri Jakarta, 2023)
The Covid-19 pandemic has changed various community activities including in the world of education, where students and teachers are required to be able to adapt in life and be able to master essential material in every subject. Electrochemistry is a branch of chemistry that studies the relationship between chemical reactions and electrical energy, namely the transfer of electrons that occur. The material about electroplating is part of electrochemistry, namely about electrolytic cells, where students must know the reactions that occur at the negative electrode (cathode) and positive electrode (anode) as well as the solution used for gilding and the object to be plated. The complexity of the material in electrochemistry makes the teacher think hard how to make learning activities in class fun and memorable so that the learning material is remembered by students. One way to make learning activities in class come alive is to do practicum. In this study the authors carried out a different practicum from the previous year, namely gilding(electroplating)the metalbrought by the students and presenting the results in video form. The research subjects were 36 students of class XII IPA1 at MAN 10 Jakarta. Before practicum activities, the teacher gives Student Activity Sheets (SAS) so that students understand the steps of practicum activities to be carried out. In the implementation of practicum activities, it begins with the Pretest, practicum electroplating and making Chemistry wallmagazines and ends with the Posttest. At the end of the assignment, students make a video presentation of the results of the metal plating they have done by showing chemistry wall magazines andpractical explanations alsoanswers thequestions from the SAS. The final result obtained is that students enjoy learning activities and get increased results from pre to pot test from the average score 65 becomes 93,06, and have directed communication skills in video presentation based on the wall magazines they have made related to the concept of electrolytic cells.